Egypt’s Religious and Intellectual Influence on Malay Society - Othman, Mohammad Redzuan (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
From the late 19th and early 20th centuries, first modern Egypt began to emerge as an important contributor to the development of religious and intellectual thought in Malay society, in addition to certain influences coming from Turkey and the Hijaz. One of the earliest aspects of the Egyptian contribution to this development perhaps came as a result of its modernization which was related to its book-publishing industry. The development of the industry began 1822 when Muhammad Ali as part of his modernisation programme requested the setting up of printing press at Bulaq in Cairo. Taking advantage of the facilities available, since the late 19th century, a considerable number of religious books used in Islamic teaching all over the Malay World were published there. One of the earliest and most active publishers to produce such religious books in Malay was Mustafa al-Babi al-Halabi, who founded his publishing house in 1859 near the al-Azhar Mosque. He however, started the venture of publishing Malay books in the late nineteenth century though the efforts of Shaykh Wan Ahmad bin Muhammad Zain al-Fatani. The latter proof-read and annotated that Malay religious books to ensure their correctness and comprehensiveness.